2018
DOI: 10.1016/j.cell.2018.06.048
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Recent Selection at FOXP2 among Diverse Human Populations

Abstract: FOXP2, initially identified for its role in human speech, contains two nonsynonymous substitutions derived in the human lineage. Evidence for a recent selective sweep in Homo sapiens, however, is at odds with the presence of these substitutions in archaic hominins. Here, we comprehensively reanalyze FOXP2 in hundreds of globally distributed genomes to test for recent selection. We do not find evidence of recent positive or balancing selection at FOXP2. Instead, the original signal appears to have been due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 73 publications
0
70
0
1
Order By: Relevance
“…For instance, animal vocalizations were thought merely to reflect the emotional arousal of the producer and thus not to represent intentional communication (Tomasello, 2008). Recent research, however, not only shows that language might be much older than previously recognized (Krause et al, 2007;Dediu & Levinson, 2013;Atkinson et al, 2018), but also is best regarded as an 'evolutionarily stratified system' (i.e. consisting of different abilities of different evolutionary origins; Levinson & Holler, 2014).…”
Section: Cognitive Mechanisms Identified In Non-human Gestures Amentioning
confidence: 99%
“…For instance, animal vocalizations were thought merely to reflect the emotional arousal of the producer and thus not to represent intentional communication (Tomasello, 2008). Recent research, however, not only shows that language might be much older than previously recognized (Krause et al, 2007;Dediu & Levinson, 2013;Atkinson et al, 2018), but also is best regarded as an 'evolutionarily stratified system' (i.e. consisting of different abilities of different evolutionary origins; Levinson & Holler, 2014).…”
Section: Cognitive Mechanisms Identified In Non-human Gestures Amentioning
confidence: 99%
“…Functional studies also showed that mice carrying a "humanized" version of FOX2 display qualitative changes in ultrasonic vocalization 13 . However, these reports targeting only specific genes sometimes provide contradictory results 14 and other studies have reported a greater sequence conservation of the brain protein-coding genes compared to other tissues [15][16][17] , suggesting that the main substrate of evolution in the brain reside in regulatory changes of gene expression [18][19][20] and splicing 21 . It was also shown that more genes underwent positive selection in chimpanzee evolution than in human evolution contradicting the widespread brain-gene acceleration hypothesis of human cognition origins 22 .…”
Section: Introductionmentioning
confidence: 96%
“…The FOXP2 locus encodes a brain-expressed transcription factor strongly implicated in the evolution of speech and language but recent studies report no evidence of recent selection in humans. 45 Nevertheless, FOXP2 is consistently implicated in the human ability to communicate via complex speech. 37 Additionally, we uncovered multiple genetically correlated traits shared between ADHD and PhoneUse in the combined and sex-stratified cohorts, including "age at first sexual intercourse" and "risk taking."…”
Section: Discussionmentioning
confidence: 99%